Effect of different temperature regimes on fungal decay of inoculated July Elberta peaches - J.L. KAUL, A.N. CHANDRANI and (Indian Phytopathology, 2002)
Sound July Elberta peaches of uniform size were inoculated with the test fungi in lots using the Lancet method and stored according to the following temperature regimes: A: 4 days at 5é³¦ + 6 days at 25? B: 1 day at 5?+ 5 days at 20?+ 4 days at 30? C: 6 days at 25é³¦ + 4 days at 30? D: 5 days at 25é³¦ + 5 days at 30? E: 10 days at 20? F: 10 days at 30? The rot development was recorded regularly up to 10 days. Rhizopus stolonifer was the fastest spreading and most conspicuous fungus, followed by Monilinia laxa, Aspergillus niger and Penicillium expansum. The results indicated that the transit and marketing of peaches at 25 to 30? would result in maximum rotting, but the deterioration of fruit could be prevented by holding them for 4 days at 4-5?and these fruits could then be despatched at a transit temperature of 25?and marketed within the lag period of 6 days.